Improved current control scheme with online current distribution and DFA regulation for switched reluctance generator. Issue 3 (2nd January 2018) - Wang, Qing; Chen, Hao; Dou, Yuyu; Abbas, Saleem
Abstract : In this study, an improved phase current control scheme (CCS) for switched reluctance generator is developed and evaluated. The objective of proposed CCS is to find the most efficient operating point according to output power command directly and shorten the online tuning process. The CCS is augmented with an online phase current distributing block (OCDB) and a dynamic firing angle regulator (DFAR). In OCDB, phase current is distributed online to minimise copper loss by maximising the average‐torque–ampere ratio. In DFAR, firing angles are processed according to actual phase current and current command. Improvements in current responses by augmenting DFAR are verified by simulations and experiments. In the end, the proposed CCS is employed in an output power controller for practical applications. Experimental results show that the proposed CCS has good dynamic response and finds the most efficient operating point directly.